Biochar as a tool for the improvement of soil and environment - Kabir, Ehsanul; Kim, Ki-Hyun; Kwon, Eilhann E. (Frontiers in Environmental Science, 2023)
Biochar is a versatile and sustainable tool for agricultural and environmental remediation due to its unique physicochemical properties in terms of soil fertility, nutrient retention, and water-holding capacity. As a stable carbon-rich material, biochar promotes plant growth and increases crop yields by enhancing microbial activity. It can also be used as a sorbent for removing pollutants such as heavy metals, organic contaminants, and nutrients from soil and water systems. However, the utility of biochar in soil and its ecological impact can be affected by the combined effects of many variables. This paper discusses the effects of biochar application on soil properties and its potential to mitigate various environmental challenges by enhancing soil composition, augmenting water accessibility, and removing pollutants as part of efforts to promote sustainable agriculture based on recent findings. These findings are expected to improve the utility of biochar in farming while contributing to the mitigation of climate change in diverse routes (e.g., by sequestering atmospheric carbon, improving soil quality, and reducing greenhouse gas emissions). This paper offers a promising opportunity to help harness the power of biochar and to pave the way for a more sustainable and resilient future.